As tonalidades líricas dos contos de Júlio Dinis - Vicente, Fernanda Monteiro (2012)
It is difficult to integrate Júlio Dinis’s short stories into a unique narrative genre due to their characteristics. In Júlio Dinis’s short stories there are always elements riddled with an unquestionable lyricism. It is not only about the dominance of the poetic function, as defined in Jacobson’s terms, but also about an understanding of particular categories as diverse as space, time, characters, the narrator or the role assigned to the reader.